Effect of electroslag remelting on non-metallic inclusions in H11 tool steel - Burja, Jaka; Tehovnik, Franc; Godec, Matjaž; Medved, Jožef; Podgornik, Bojan; Barbič, Rok (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The effect of the electroslag remelting on the non-metallic inclusion content and composition is studied in this paper. It was found that in the observed case an approximate 50 % decrease in the non-metallic inclusion content occurred during the electroslag remelting. A change in the chemical composition of the non-metallic inclusions has been observed, the aluminum and calcium content is increased. The complexity of the inclusions also increases as there are less single phase inclusions after the electroslag remelting process. Based on the result and thermodynamic assessment of non-metallic inclusion formation, a mechanism for inclusion behavior during electroslag remelting has been proposed.Keywords: Electroslag remelting (ESR), non-metallic inclusions, steelmaking, thermodynamics of steel, clean steel